Sleep syncope—A systematic review - Raj, Priya L.; Sheldon, Robert S.; Lorenzetti, Diane; Jardine, David L.; Raj, Satish R.; Vandenberk, Bert (Frontiers in Cardiovascular Medicine, 2022)
Background Sleep syncope is a subtype of vasovagal syncope in which patients experience syncope after awakening from their sleep. The aim was to investigate the association of clinical characteristics and gastrointestinal symptoms with syncope, as well as the body position in which symptoms began. Methods A systematic search of studies was performed in MEDLINE and EMBASE without language restrictions, from inception to 9 January 2022. Studies were included if they reported data on the proportion of patients who experienced symptoms (nausea, vomiting, abdominal pain, and diarrhea) associated with syncope. Results Data were included for 116 patients in 13 studies. Patients were 46.9 ± 4.3 years and 61.4% were female. In 52.5% of patients, a supine body position at the time of syncope was reported. A history of phobias was reported by 67.6% of patients, and 96.5% of patients also had typical daytime vasovagal syncope. In the 5 studies reporting the results of head-up tilt testing (n = 77), 90.9% of patients had positive tests. Gastrointestinal symptoms were present in the majority of patients with reported rates of 65.6% for upper gastrointestinal symptoms and 86.0% for lower gastrointestinal symptoms. Conclusion Patients with sleep syncope patients are predominantly female with a history of daytime vasovagal syncope. Gastrointestinal symptoms are present in the majority of patients and is therefore an important feature of sleep syncope.